The Role of Store Atmosphere and Price Discount in Driving Repurchase Intention: The Mediating Effect of Customer Satisfaction - Elika Rani; Wenny Pebrianti; Harry Setiawan; Bintoro Bagus Purmono; Ahmadi (Journal of Educational Management Research, 2026)
This study aims to examine the effects of store atmosphere and price discount on repurchase intention, both directly and indirectly through customer satisfaction as a mediating variable. This research employed a quantitative approach by collecting data through questionnaires from 150 respondents. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the proposed relationships among variables. The results indicate that store atmosphere and price discount have significant effects on repurchase intention. Furthermore, customer satisfaction plays a significant mediating role in strengthening the relationship between store atmosphere, price discount, and repurchase intention. The findings highlight that an attractive shopping environment and competitive pricing strategies are essential factors in enhancing customer satisfaction and encouraging repeat purchases. This study implies that retailers should prioritize improvements in store atmosphere and value-based promotional strategies to build long-term customer loyalty and increase repurchase intention.